2020
DOI: 10.1111/ppl.13044
|View full text |Cite
|
Sign up to set email alerts
|

Internal aeration and respiration of submerged tomato hypocotyls are enhanced by ethylene‐mediated aerenchyma formation and hypertrophy

Abstract: With the impending threat that climate change is imposing on all terrestrial ecosystems, the ability of plants to adjust to changing environments is, more than ever, a very desirable trait. Tomato (Solanum lycopersicum L.) plants display a number of responses that allow them to survive under different abiotic stresses such as flooding. We focused on understanding the mechanism that facilitates oxygen diffusion to submerged tissues and the impact it has on sustaining respiration levels. We observed that, as flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In tomato plants, which are susceptible to flooding stress, several adaptive responses help to mitigate the deleterious effects of hypoxia in roots. Among them, the ethylene-mediated aerenchyma formation, the stem hypertrophy, and the formation of adventitious roots facilitate O 2 transport and may act as an escape mechanism enabling tolerance of hypoxia ( Mignolli et al , 2020 ). Genes coding for proteins with a potential role in aerenchyma formation have been identified using an RNA-Seq approach in tomato roots under hypoxia ( Safavi-Rizi et al , 2020 ).…”
Section: Diverse Conditions Causing Hypoxia and Downstream Responsesmentioning
confidence: 99%
“…In tomato plants, which are susceptible to flooding stress, several adaptive responses help to mitigate the deleterious effects of hypoxia in roots. Among them, the ethylene-mediated aerenchyma formation, the stem hypertrophy, and the formation of adventitious roots facilitate O 2 transport and may act as an escape mechanism enabling tolerance of hypoxia ( Mignolli et al , 2020 ). Genes coding for proteins with a potential role in aerenchyma formation have been identified using an RNA-Seq approach in tomato roots under hypoxia ( Safavi-Rizi et al , 2020 ).…”
Section: Diverse Conditions Causing Hypoxia and Downstream Responsesmentioning
confidence: 99%
“…However, after this early peak, ADH activity decreases to levels that are even lower than in control plants (Figure S3). It is plausible, therefore, that the re‐oxygenation of submerged tissues resulting from aerenchyma formation might be responsible for lowering ADH activity and fermentative metabolism (Mignolli et al, 2020; Zabalza et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As the availability of substrate (sucrose) increases, respiration is fuelled creating a sucrose gradient that results in a sustained transport of carbohydrates to the submerged hypocotyl (Figure 6). Sugar accumulation in the hypocotyl could fulfil the energy needs for adventitious root development, aerenchyma formation (Figure S6A,B; Takahashi et al, 2018; Qi et al, 2020) or cortical cell expansion (González, Roitsch, & Cejudo, 2005; Mignolli et al, 2020). The baffling question is why the same increase in respiration and sugar build‐up occurs in waterlogged plants, where neither aerenchyma formation nor ARs development nor stem hypertrophy are taking place (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boosted ethylene biosynthesis, followed by ethylene entrapment by water in proximity to submerged tissues, is able to induce important anatomical and biochemical changes in submerged organs. Ethylene‐mediated plant adaptations to flooded environments include: aerenchyma formation as seen in maize, rice and tomato (Yamauchi et al 2016, Mignolli et al 2020), adventitious roots formation as observed in species like Solanum dulcamara and tomato (Vidoz et al 2010, Dawood et al 2016), petiole hyponasty thoroughly studied in Rumex and Arabidopsis (van Veen et al 2013), and internode elongation noted in deep‐water rice cultivars (Hattori et al 2009). In addition, ethylene seems to be a necessary determinant of alcohol dehydrogenase induction and the initiation of the fermentative pathway in hypoxic organs (Peng et al 2001).…”
Section: Introductionmentioning
confidence: 99%